2020
DOI: 10.3389/fbioe.2020.589094
|View full text |Cite
|
Sign up to set email alerts
|

Desktop-Stereolithography 3D Printing of a Polyporous Extracellular Matrix Bioink for Bone Defect Regeneration

Abstract: Introduction: Decellularized tendon extracellular matrix (tECM) perfectly provides the natural environment and holds great potential for bone regeneration in Bone tissue engineering (BTE) area. However, its densifying fiber structure leads to reduced cell permeability. Our study aimed to combine tECM with polyethylene glycol diacrylate (PEGDA) to form a biological scaffold with appropriate porosity and strength using stereolithography (SLA) technology for bone defect repair. Methods: The tECM was produced and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Additionally, in vivo studies showed that glucose is lowered within 60 min due to fast insulin action with steady-state plasma glucose in transdermal injection when compared to subcutaneous injection [45]. Decellularized tendon extracellular matrix (tECM) is essential for bone regeneration and, in a study, tECM and PEGDA scaffolds with an appropriate pore size and strength were fabricated using SLA and suggested that 3D printed polyporous PEGDA/tECM (3D-pPES) scaffolds can be effectively used for bone defect treatment based on the data, which showed an increased cell migration potential, enhanced osteogenic differentiation, and effective calvarial defect repair capacity in a rat model of 3D-pPES when compared to the control [46].…”
Section: Sla-based Printingmentioning
confidence: 99%
“…Additionally, in vivo studies showed that glucose is lowered within 60 min due to fast insulin action with steady-state plasma glucose in transdermal injection when compared to subcutaneous injection [45]. Decellularized tendon extracellular matrix (tECM) is essential for bone regeneration and, in a study, tECM and PEGDA scaffolds with an appropriate pore size and strength were fabricated using SLA and suggested that 3D printed polyporous PEGDA/tECM (3D-pPES) scaffolds can be effectively used for bone defect treatment based on the data, which showed an increased cell migration potential, enhanced osteogenic differentiation, and effective calvarial defect repair capacity in a rat model of 3D-pPES when compared to the control [46].…”
Section: Sla-based Printingmentioning
confidence: 99%
“…However, its dense fibrous structure decreases cell permeability and becomes a constraint obstacle for bone scaffolds. Yunxiang Luo et al [21] generated tendon extracellular matrix (tECM) and combined it with polyethene glycol diacrylate (PEGDA). They used stereolithography (SLA) technology to form 3D printed polyporous PEGDA/tECM scaffolds (3D-pPES).…”
Section: Bioactive Glassmentioning
confidence: 99%
“…Despite the clear advantages associated with extrusion-based printing, this technique lacks in resolution. Since cell activity is influenced by topographical cues, exploring techniques with greater resolution, such as fused-deposition modeling [ 11 , 18 , 21 ], and stereolithography [ 6 ], that allow increased control over this feature should be addressed [ 42 ]. Another alternative for obtaining more complex structures and with important cues for cellular interaction and vascularization of the micro-tissue formed is the combination of extrusion bioprinting with other emerging technologies such as microfluidic to simulate real tissue functions, where bioinks can be printed with different types of cells [ 87 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Biofabrication has been defined as a process through which biomaterials with living cells and biological cues are used as building blocks to manufacture functional biological systems [ 1 , 2 , 3 , 4 ]. This field of cutting-edge technologies include three-dimensional (3D) bioprinting [ 5 , 6 , 7 ], electrospinning [ 8 , 9 ], or bio-plotting [ 10 ], which generate different functional constructs depending on the intended bio-medical application [ 11 ]. 3D bioprinting in particular, is one of the cutting-edge technologies available in this field which, according to the recent trends, has exponentially grown at the start of the year 2000 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%